2022
DOI: 10.1038/s41598-022-17402-w
|View full text |Cite
|
Sign up to set email alerts
|

Understanding complex genetic architecture of rice grain weight through QTL-meta analysis and candidate gene identification

Abstract: Quantitative trait loci (QTL) for rice grain weight identified using bi-parental populations in various environments were found inconsistent and have a modest role in marker assisted breeding and map-based cloning programs. Thus, the identification of a consistent consensus QTL region across populations is critical to deploy in marker aided breeding programs. Using the QTL meta-analysis technique, we collated rice grain weight QTL information from numerous studies done across populations and in diverse environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
2
12
1
Order By: Relevance
“…These MQTLs were unevenly distributed on seven chromosomes, with the highest number of MQTLs on chromosome 2H (18) and the lowest on chromosome 6H (9), which was generally consistent with the distribution of the initial QTL on the chromosomes (Fig 3C). The distribution was inconsistent with the previously reported MQTLs for yield-related traits in barley, which were similar in form to the initial QTL [24].…”
Section: Plos Onesupporting
confidence: 79%
See 1 more Smart Citation
“…These MQTLs were unevenly distributed on seven chromosomes, with the highest number of MQTLs on chromosome 2H (18) and the lowest on chromosome 6H (9), which was generally consistent with the distribution of the initial QTL on the chromosomes (Fig 3C). The distribution was inconsistent with the previously reported MQTLs for yield-related traits in barley, which were similar in form to the initial QTL [24].…”
Section: Plos Onesupporting
confidence: 79%
“…Recently, QTL meta-analysis has been widely used for QTL integration of complex quantitative traits in different crops, such as ionome-related traits in Arabidopsis thaliana [ 14 ], grain water content, grain dehydration rate and yield-related traits in maize [ 15 , 16 ], grain weight and yield-related traits in rice [ 17 , 18 ], grain zinc and iron contents, flag leaf morphology, quality and yield-related traits in wheat [ 19 21 ]. In addition, QTL meta-analysis has also been reported for several traits in barley, such as three studies on abiotic stress tolerance traits [ 11 , 22 , 23 ], and one on yield and yield-related traits [ 24 ], in which a total of 31 MQTLs were identified, but limited by the number of QTL mapping populations and the initial QTL, the results have certain limitation and need further refinement.…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses of QTLs associated with a variety of traits have been recently conducted in different crops such as wheat ( Kumar et al, 2021 ; Kumar et al, 2022 A. C. ; Kumar et al, 2023 S. ; Saini et al, 2021 ; Saini et al, 2022 ; Tanin et al, 2022 ), rice ( Sandhu et al, 2021 ; Kumari et al, 2023 ), barley ( Akbari et al, 2022 ), common bean ( Shafi et al, 2022 ), pigeon pea ( Halladakeri et al, 2023 ), including maize ( Kaur et al, 2021 ; Sheoran et al, 2022 ; Wang et al, 2022 ; Gupta et al, 2023 ; Karnatam et al, 2023 ), for diverse traits, including both yield-related traits ( Semagn et al, 2013 ; Wang Y. et al, 2016 ; 2020 ; Chen et al, 2017 ; Zhou et al, 2020 ) and quality traits ( Jin et al, 2013 ; Dong et al, 2015 ). However, there is currently no comprehensive study on the genomic regions influencing both grain quality and yield in maize.…”
Section: Discussionmentioning
confidence: 99%
“…Several MQTL analysis studies have been carried out for drought tolerance in different field crops like maize (Semagn et al, 2013), wheat (Acuña-Galindo et al, 2015 and barley (Zhang, Shabala, et al, 2017). Recently, MQTL analysis studies have been reported in rice focusing on yield and other parameters under unstressed conditions (Anilkumar, Sah, Muhammed Azharudheen, et al, 2022;Khahani et al, 2020)…”
Section: Identification Of Qtl Controlling Drought Tolerance In Ricementioning
confidence: 99%
“…Several MQTL analysis studies have been carried out for drought tolerance in different field crops like maize (Semagn et al, 2013), wheat (Acuña‐Galindo et al, 2015) and barley (Zhang, Shabala, et al, 2017). Recently, MQTL analysis studies have been reported in rice focusing on yield and other parameters under unstressed conditions (Anilkumar, Sah, Muhammed Azharudheen, et al, 2022; Khahani et al, 2020), whereas Swamy et al (2011) and Trijatmiko et al (2014) made significant contribution in detecting MQTL for yield and related traits under water deficit conditions in rice. Selamat and Nadarajah (2021) complied the 653 QTL identified for drought‐related traits in rice across the globe and developed a consensus map to identify 70 MQTL for drought traits over all chromosomes of rice.…”
Section: Breeding For Drought Tolerancementioning
confidence: 99%